The Switherby pilgrims - Spence, Eleanor; Gray, Corinna (London : Oxford University Press, 1967)
In 1825, concerned for the future of her ten orphan charges in the grim factory towns of their native England, Miss Arabella Braithewaite, known to the children as Missabella, decides to take a land grant in Australia and makes the long, daunting journey with her wards to the austere bush country of New South Wales.
Keywords: Orphans -- Fiction; Immigrants -- Fiction; Frontier and pioneer life -- Fiction; Australia -- History -- 1788-1851 -- Fiction